Proceedings Of The Dalgarno Celebratory Symposium : Contributions To Atomic, Molecular, And Optical Physics, Astrophysics, And Atmospheric Physics. (World Scientific, 2009)
This unique volume is a compendium of scientific contributions inspired by the work of Alex Dalgarno in the fields of atomic, molecular, and optical physics, astrophysics, astrochemistry, and atmospheric physics. The book should be of particular value to the practitioners in these fields. Sample Chapter(s). Chapter 1: The Transition From Mathematician to Astrophysicist (1,431 KB). Contents: Calculations of Atomic and Molecular Properties; Astrochemistry; Interstellar Medium and Molecular Astrophysics; Atomic and Molecular Processes in the Solar System and Planetary Atmospheres; Ultra-Cold Coll.